Right Internal Jugular Vein Access for Micra Leadless Pacemaker Implantation in a High-Risk Patient with Severe Iliac Vein Stenosis: A Case Report - Xu H; Qian J; Pan W; Fan J (International Medical Case Reports Journal, 2025)
Haixiang Xu, Jianfeng Qian, Wen Pan, Jianhua Fan Department of Cardiology, Kunshan Hospital of Traditional Chinese Medicine Affiliated to Yangzhou University, Suzhou, People’s Republic of ChinaCorrespondence: Jianhua Fan, Department of Cardiology, Kunshan Hospital of Traditional Chinese Medicine Affiliated to Yangzhou University, Suzhou, People’s Republic of China, Email fjhheart@126.comBackground: Leadless pacemakers offer a promising alternative to traditional transvenous pacemakers, especially in patients with complex vascular anatomy or a high risk of infection. Conventional access routes may be compromised in patients with significant venous stenosis or prior vascular interventions, requiring alternative strategies for device implantation.Case Presentation: We report the case of a 74-year-old female with sick sinus syndrome, chronic kidney disease, type 2 diabetes, and severe bilateral iliac vein stenosis, who was deemed high-risk for conventional pacemaker implantation. After failed attempts through both femoral veins, the right internal jugular vein (RIJV) was successfully used as an alternative access route for Micra leadless pacemaker implantation. The procedure was performed under ultrasound and fluoroscopic guidance without complications. Post-procedure, the pacing threshold was 0.75 V, sensing was 8.5 mV, and impedance was 760 Ω, all within normal limits.Conclusion: This case highlights the feasibility and safety of using the right internal jugular vein as an alternative access route for leadless pacemaker implantation in high-risk patients when femoral access is not possible. This approach provides a valuable option for patients with complex venous anatomy, contributing to the broader application of leadless pacing technology.Keywords: micra leadless pacemaker, right internal jugular vein, iliac vein stenosis, high-risk patient, alternative access